Characterization and cancer risk assessment of VOCs in home and school environments in Gran La Plata, Argentina - Colman Lerner, Jorge Esteban (2018)
Three areas are highlighted in Gran La Plata, Argentina: industrial, urban, and residential. In this work, the levels of volatile organic compounds (VOCs) in indoor air of homes and schools in those areas were analyzed, through the use of passive monitors. The study period is between 2007 and 2010. Higher levels of VOCs were found in homes and schools in the industrial zone, higher than the levels corresponding to urban and residential. Taking into account the relationship between indoor and outdoor levels of VOCs, they have ratios (I/O) between 1.5 and 10 are evidenced contributions of emission sources of VOCs both indoor and outdoor. Complementarily, we estimated the life time cancer risk (LCR) for benzene, styrene, trichloroethylene, and tetrachloroethylene in children who spend their time mostly in such indoor environments. The results show high LCR values for benzene, which exceed acceptable values for the US EPA.